Pelatihan Pembuatan Buku Cerita Menggunakan Artificial Intelligence Bagi Guru PAUD - Nurhayati Nurhayati; Amrullah Amrullah; Armina M; Hamzia Marie; Zakiyyatul Imamah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
A teacher's essential competency is the ability to teach skillfully. In this day and age, many media can be utilized to make the learning process engaging and less monotonous, including leveraging technological developments. Many early childhood education (PAUD) teachers still have limited understanding of technology, including the use of Artificial Intelligence (AI), specifically in storybook creation. This community service program aims to improve the competence of PAUD teachers in creating storybooks using AI. By being able to create their own storybooks, teachers are no longer entirely dependent on books available on the market. They can adapt stories to suit students' needs and develop more personalized and innovative learning resources. Therefore, PAUD teachers in Palu City must be trained in creating storybooks using AI. The method used to address the problems experienced by partners is a training method using experiential learning techniques. The learning method consists of a pretest-posttest design with 15 participants. The results of the community service were analyzed using a descriptive quantitative approach. The results of the community service program found a significant increase in AI conceptual knowledge by 69.2%, technical skills by 93.2%, and perception and application by 68.6%. This activity successfully improved teachers' competence in using artificial intelligence to create learning media.